Periodontal Reasons for Tooth Extraction in a Group of Greek Army Personnel - Nikolaos Andreas Chrysanthakopoulos (Tabriz University of Medical Sciences, 2011)
Background and aims. The aim of this study was to investigate the prevalence of permanent teeth extracted due to periodontal disease and its relation to age, military rank, and type of extracted teeth due to periodontal and non-periodontal reasons among a group of Greek Army personnel attending a military dental practice. Materials and methods. Study population consisted of 509 officers, non-commissioned officers and soldiers, aged 18 to 44 years from a military dental hospital in Greece. The reasons for extractions of teeth for a period of two years were obtained, including aspects such as age, military rank and the type of teeth extracted due to periodontal and non-periodontal reasons. Data were analyzed using chi-squared test. Results. The total number of extracted teeth was 1,231, of which 34.4% were extracted because of periodontal reasons, 32.2% for dental caries and 33.4% for other reasons. The average number of extracted teeth due to periodontal disease showed an increase with age. Maxillary and mandibular first and second molars were the most frequently extracted teeth due to periodontal reasons; however, the anterior teeth of both jaws with mobility (grade III), the same teeth with attachment loss (≥5.0 mm) and the posterior teeth of both jaws with furcation involvement (grade IV) were the most frequently extracted teeth due to periodontal reasons. Conclusion. Although the goal of the WHO regarding the reduction of dental caries was accomplished, periodontal disease was still the main cause of tooth extraction and showed an increase with age.